Impact of a caregiver empowerment intervention within an age friendly village model on depression and loneliness in older adults: A Quasi Experimental Study - Fredy Akbar K; Syamsidar Syamsidar; Adi Hermawan (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Depression and loneliness are major contributors to morbidity and reduced quality of life among older adults, particularly in rural community settings where access to mental health services is limited. Strengthening caregiver capacity may represent a scalable strategy to improve psychological wellbeing. This study aimed to evaluate the effectiveness of a community-based caregiver empowerment program in reducing depressive symptoms and loneliness among older adults living in an age-friendly village in Indonesia. Research Methodology: A quasi-experimental nonequivalent pretest–posttest control group design was employed. Seventy-two community-dwelling older adults (n=36 in the intervention group; n=36 in the control group) were recruited using purposive sampling. The intervention consisted of a 6-week structured caregiver empowerment program including psychoeducation, therapeutic communication training, emotional support strategies, and supervised home visits. Depression was measured using the Geriatric Depression Scale (GDS-15) and loneliness using the UCLA Loneliness Scale. Data were analysed using paired and independent t-tests and multiple linear regression (α = 0.05). Results: The intervention group demonstrated significantly greater reductions in depressive symptoms (β = -2.88; 95% CI: -3.74 to -2.02; p < 0.001) and loneliness (β = -3.97; 95% CI: -4.98 to -2.96; p < 0.001) compared with the control group. Large effect sizes were observed for both outcomes. Conclusion: The caregiver empowerment program was effective in improving psychological outcomes among community-dwelling older adults. Integrating structured caregiver training into age-friendly villages and primary health care services may provide a scalable, evidence-based strategy to strengthen mental health resilience in ageing populations.